Proceedings of the Eye Tracking Research &Amp; Applications Symposium on Eye Tracking Research &Amp; Applications - ETRA'2004 2004
DOI: 10.1145/968363.968370
|View full text |Cite
|
Sign up to set email alerts
|

Eye gaze patterns differentiate novice and experts in a virtual laparoscopic surgery training environment

Abstract: Visual information is important in surgeons' manipulative performance especially in laparoscopic surgery where tactual feedback is less than in open surgery. The study of surgeons' eye movements is an innovative way of assessing skill, in that a comparison of the eye movement strategies between expert surgeons and novices may show important differences that could be used in training. We conducted a preliminary study comparing the eye movements of 5 experts and 5 novices performing a one-handed aiming task on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
125
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(143 citation statements)
references
References 17 publications
18
125
0
Order By: Relevance
“…Information such as this would be very helpful in places where simulation is being used to aid in resident and medical student remediation. Having the ability to analyze what the participant sees and focuses on can help with redirection and identification of knowledge translation issues [20][21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
“…Information such as this would be very helpful in places where simulation is being used to aid in resident and medical student remediation. Having the ability to analyze what the participant sees and focuses on can help with redirection and identification of knowledge translation issues [20][21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has revealed differences in the gaze control strategies of experienced and novice laparoscopic surgeons [3,4]. Novices, who are still developing the sensory-motor mapping rules for laparoscopy, use visual feedback to check on the effect of their movements, and so exhibit a gaze strategy that switches between tracking their tool movements and fixating the target to be manipulated (a switching strategy) [3,5]. Experienced surgeons, who have developed the necessary sensory-motor mapping rules, primarily fixate the target without the need to check their tool locations (a target-locking strategy) [3,4].…”
mentioning
confidence: 99%
“…Gaze tracking has been used previously to find comparisons between novices and experts; e.g. during Visual Flight Rules flight [6], during laparoscopic surgery [8], working within a Learning Management System [14], while playing chess [3], and within collaborative environments [9]. It has been found to be a good indicator of the "Yes!"…”
Section: Introductionmentioning
confidence: 99%